Unlocking Sustainable Growth: The Role of Artificial Intelligence Adoption in Jordan Retail Sector, Moderated by Entrepreneurial Orientation - Al-Ramahi, Nancy; Kreishan, Fuad M.; Hussain, Zahid; Khan, Arman; Alghizzawi, Mahmoud; AlWadi, Belal Mahmoud (International Review of Management and Marketing, 2024)
Although businesses are under pressure to consistently improve both their capacities and business processes, the artificial intelligence (AI) revolution is seen as an appealing company approach that has attracted attention. By offering improved company structures, the application of AI technology has the potential to significantly alter company procedures while also lessening the impact of outside catastrophes. Additionally, using AI can enhance the socioeconomic circumstances of a particular area and have a positive impact on the social worth and economic sustainability of businesses. Few studies have been conducted recently on the use of AI to support businesses at various stages of development and sustainability. In addition, there isn’t much research that shows that the retail sector can benefit from the use of various modern AI technologies. To bridge this gap, this investigation looks into the moderating effect of entrepreneurial orientation. A theoretical framework was established using the assistance of the resource-based view (RBV) and dynamic capability view (DCV) assumptions, in addition to a survey of the available literature. The PLS-SEM method was used in this paper and got 311 respondents from Amman, Jordon retail sector. The findings show that the industry needs to make strategies for social justice and economically favorable approaches that have a beneficial impact by adopting AI approaches. This paper also shows that EA has a moderate impact on performance connections within the industry.